Distributional differences in the time horizon of executive compensation - Michael Haylock (Empirical Economics, 2021)
The aim of executive compensation plans is to incentivize executives to maximize long-term firm value. Past research shows that executives' pay is determined by short-term stock performance to a substantial degree. This paper tests for distributional differences in the time horizon of the performance–pay relation, controlling for executive-firm fixed effects in a quantile regression framework. I identify short-term and long-term firm and industry performance using a filter and estimate distributional differences in the short-term and long-term performance–pay relation using method of moments–quantile regression (Machado and Santos Silva in J Econ 213:145–173, 2019). I find the right tail of the conditional total compensation distribution has a more long-term-oriented performance–pay relation than the left tail. By contrast, the right tail of the conditional accumulated wealth distribution has more short-term-oriented performance–pay relation than the left tail. Results show that asymmetry in short-term firm performance–pay relations may exist, but do not vary across the conditional distribution.
Keywords: M12; M52; C23; 330; Executive compensation; Method of moments–quantile regression; Quantile regressions; Short-termism; Time horizon; Benchmarking; Top wage distribution